A rare case report: co-occurrence of two types of lung cancer with hamartoma and pulmonary tuberculosis - Kang, Jianxiong; Wang, Mu; Hua, Peiyan; Wang, Bin (Frontiers in Oncology, 2023)
With the widespread use of low-dose chest Computed Tomography (CT), lung nodules are being increasingly detected. Common pulmonary conditions such as lung adenocarcinoma, lung squamous cell carcinoma, and tuberculosis are typically diagnosable through imaging examinations.Nevertheless, when multiple types of lung cancer are combined with other benign tumors, how can an accurate diagnosis be made? In this report, we present a rare case of a patient with the simultaneous occurrence of lung adenocarcinoma, lung squamous cell carcinoma, pulmonary tuberculosis, and pulmonary hamartoma, which has not been previously reported. This patient underwent surgical intervention in the Department of Thoracic Surgery at the Second Hospital of Jilin University and has now fully recovered and been discharged. The patient's preoperative positron emission tomography-CT(PET-CT)results did not align with the postoperative pathological diagnosis. The imaging findings were atypical, and the pathological diagnosis was exceptionally rare.We share this case report to contribute to the accumulation of clinical experience.